Providing support to patients who wish to quit smoking. Issue 7 (5th April 2014) - Pang, Elizabeth; Stern, Myra
Abstract Smoking cessation is the most cost‐effective intervention for the prevention and treatment of smoking‐related disease. Here, the authors discuss the available products for aiding smoking cessation and how to support patients wishing to quit.